2008
DOI: 10.1111/j.1600-0714.2007.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

P21/ WAF1 and cyclin D1 variants and oral squamous cell carcinoma

Abstract: The present study did not demonstrate a significant association between CCND1 and / or P21 / WAF1 genotypes and OSCC. However, P21 protein expression in OSCC tumours is affected by P21 / WAF1 genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Genetic and epigenetic factors are associated with a susceptibility to cancer development at a young age (4,37). Alternatively, genetic and epigenetics factors may play a stronger role than HPV-16/18 infection in the development of HNSSC at an early age (38)(39)(40)(41)(42). In the current study, we did not observe differences in survival associated with age, in agreement with previous studies (4,37).…”
Section: Discussionsupporting
confidence: 82%
“…Genetic and epigenetic factors are associated with a susceptibility to cancer development at a young age (4,37). Alternatively, genetic and epigenetics factors may play a stronger role than HPV-16/18 infection in the development of HNSSC at an early age (38)(39)(40)(41)(42). In the current study, we did not observe differences in survival associated with age, in agreement with previous studies (4,37).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, after excluding five studies (Catarino et al, 2006;Gomes et al, 2008;Tsai et al, 2011;Shih et al, 2012;Sabir et al, 2013) that significantly deviated from HWE, the results were not substantially altered, indicating statistically obvious robustness in our results (Table 3).…”
Section: Quantitative Synthesismentioning
confidence: 52%
“…However, 2 papers (Huang et al, 2006;Ye et al, 2008) were ruled out for the studies on premalignant lesion instead of cancer. As a result, 17 papers (Matthias et al, 1998;Zheng et al, 2001;Deng et al, 2002;Wong et al, 2003;Monteiro et al, 2004;Nishimoto et al, 2004;Holley et al, 2005;Catarino et al, 2006;Rydzanicz et al, 2006;Sathyan et al, 2006;Gomes et al, 2008;Marsit et al, 2008;Sui et al, 2009;Jelonek et al, 2010;Tsai et al, 2011;Shih et al, 2012;Sabir et al, 2013) comprising seventeen eligible studies with 3,761 cases and 3,834 controls for CCND1 G870A as well as three eligible studies (Sathyan et al, 2006;Tsai et al, 2011;Shih et al, 2012) with 943 cases and 935 controls for CCND1 G1722C were included. With regard to CCND1 G870A, seven studies (Matthias et al, 1998;Zheng et al, 2001;Monteiro et al, 2004;Holley et al, 2005;Catarino et al, 2006;Rydzanicz et al, 2006;Jelonek et al, 2010) were performed in Caucasians and seven (Deng et al, 2002;Wong et al, 2003;Sathyan et al, 2006;Sui et al, 2009;Tsai et al, 2011;Shih et al, 2012;Sabir et al, 2013) were conducted in Asians and three …”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our study gives additional support that both smoking and aging are important factors involved in DNA methylation. In recent years, several studies have demonstrated that genetic polymorphisms are associated with susceptibility to, or protection from, cancer development (36,65,66). Until now, 13 polymorphisms were described in the coding region of gene DNMT3B according NCBI database, but the association between these genetic variations and cancer prognosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%